Prevalence of metabolic syndrome in primary health settings in Qatar: a cross sectional study - Mohamed Ahmed Syed; Ahmed Sameer Al Nuaimi; Abdul Jaleel A. Latif Zainel; Hamda Abdulla A/Qotba (BMC, 2020)
Abstract Background In Qatar, prevalence of metabolic components is significantly higher compared to other countries. It is therefore urgent to understand the prevalence of metabolic syndrome (MetS) with the goal of identifying etiologic factors in Qatar. This study was undertaken to estimate the prevalence of MetS, by age, gender and nationality within primary care settings in Qatar. In addition, it determined the independent effects of risk factors on the prevalence of MetS. Methods A cross-sectional study design was used. Data for individuals aged ≥18 and who visited a publicly funded primary health centre in Qatar during 2017 were extracted from electronic medical records and analysed. Results The findings showed that the prevalence of individual MetS components ranged between 48.5-60.3%. Overall prevalence of MetS was 48.8% (N = 62,492) in the study population. Prevalence of MetS increased with age. 50.3% of the population within the 40-49 year age group had MetS. In this age band, individuals were 5.1 times more likely of having MetS compared to the 18-29 year age group. MetS was slightly more prevalent in men (56 .7%) compared to women (42.5%). However, men were 1.33 times more likely of having MetS compared to women. The prevalence of MetS ranged between 20.6 - 60% across nationalities. It was most prevalent in Southern Asians (60%), followed by Northern Africans (50.7%) and Western Asians (excluding Qatar) (46.8%). Prevalence of MetS in Qataris was 43%. Southern Asians, Northern African and Western Asians were 1.73, 1.38 and 1.17 more likely to have MetS compared to Qataris. Conclusions The study provides essential epidemiological information required by decision makers. Although not nationally representative, this study is suggestive of a higher prevalence of MetS among a younger population, men and in Southern Asian, Northern African and Western Asian nationalities. Prevention, treatment and control of MetS is a public health problem in Qatar. More studies are needed to establish which public health interventions are likely to be effective in Qatar.